2007
DOI: 10.1261/rna.772408
|View full text |Cite
|
Sign up to set email alerts
|

Screening for engineered neomycin riboswitches that control translation initiation

Abstract: Riboswitches are genetic control elements that regulate gene expression in a small molecule-dependent way. We developed a two-stage strategy of in vitro selection followed by a genetic screen and identified several artificial small molecule-binding riboswitches that respond to the aminoglycoside neomycin. Structure-function relationships and structural probing revealed that they adopt the general neomycin-binding motif. They display no sequence similarities to in vitro selected neomycin aptamers but contain pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
216
0
8

Year Published

2008
2008
2013
2013

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 187 publications
(226 citation statements)
references
References 41 publications
(61 reference statements)
2
216
0
8
Order By: Relevance
“…Previous work has revealed that bacterial riboswitches that act on a translational level often regulate gene expression through ligand-dependent structural changes in the 59-UTR that provide or limit access to the ribosome binding site (RBS) of an RNA transcript (Nudler and Mironov 2004). This insight has inspired efforts to convert synthetic aptamers into riboswitches through rational engineering (Werstuck and Green 1998;Desai and Gallivan 2004;Suess 2005) or genetic screens and selections (Lynch et al 2007;Topp and Gallivan 2008;Weigand et al 2008). Here, we report that synthetic riboswitches that modulate translation in bacteria can be located within the coding region of a gene and that opportunities for developing new riboswitches may be enhanced by placing fewer restrictions on the expected mechanisms of RNA-based genetic regulation.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has revealed that bacterial riboswitches that act on a translational level often regulate gene expression through ligand-dependent structural changes in the 59-UTR that provide or limit access to the ribosome binding site (RBS) of an RNA transcript (Nudler and Mironov 2004). This insight has inspired efforts to convert synthetic aptamers into riboswitches through rational engineering (Werstuck and Green 1998;Desai and Gallivan 2004;Suess 2005) or genetic screens and selections (Lynch et al 2007;Topp and Gallivan 2008;Weigand et al 2008). Here, we report that synthetic riboswitches that modulate translation in bacteria can be located within the coding region of a gene and that opportunities for developing new riboswitches may be enhanced by placing fewer restrictions on the expected mechanisms of RNA-based genetic regulation.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, insertion of aptamers into the 5′-UTRs of bacterial or eukaryotic mRNAs (9)(10)(11)(12), splice sites within introns of eukaryotic pre-mRNA (13,14), or coupling of aptamers to ribozymes (15,16) have shown significant potential for small-molecule modulation of gene expression. However, there are currently very few aptamers, generated by in vitro selection, that are selective for ligands with desirable physicochemical and pharmacokinetic properties (8).…”
mentioning
confidence: 99%
“…However, a major drawback in the analysis of large-scale metagenomic sequence data sets is the isolation of functional elements, given that these RNAs tend to: (1) be short (often mistaken for chemically degraded RNAs), (2) lack open reading frames, and (3) sometimes evolve rapidly at the sequence levels while still conserving structure that is integral to their function. 107,108 Need for novel in vitro RNA stabilization methods Although new sensing capabilities of natural and unnatural ligands have been successfully engineered into RNAs via in vitro and in vivo molecular evolution approaches, [109][110][111] the ability to use these molecules by incorporating them into more complex systems and devices represents a bigger practical challenge. 23 All potential RNA Synthetic Biology applications require reproducible and controlled molecular stability, especially when activity is required outside the native cellular host and in the context of other biological and inorganic materials.…”
Section: Unexplored Diversity Of Natural Riboswitches In Living Systemsmentioning
confidence: 99%